Safety and efficacy of intrathecal rituximab in children with B cell lymphoid CD20+ malignancies: An international retrospective study. Issue 5 (4th April 2016) - Ceppi, Francesco; Weitzman, Sheila; Woessmann, Wilhelm; Davies, Kimberly; Lassaletta, Alvaro; Reismüller, Bettina; Mellgren, Karin; Uyttebroeck, Anne; Maia, Iris; Abdullah, Shaker; Miakova, Natasha; Glaser, Darryl; et al.
Abstract : Central nervous system (CNS) involvement in patients with mature B non‐Hodgkin lymphoma, post‐transplantation proliferative disorder and acute lymphoblastic leukemia confers a significantly inferior prognosis as compared to patients without CNS disease. Intrathecal (IT) or intraventricular administration of rituximab is an option for this group of patients. We report 25 children with CNS involvement of CD20+ B lymphoid malignancies who received in total 163 IT/intraventricular rituximab doses. The median number of doses received by each patient was 6, with a median dose of 25 mg. The most common adverse events were Grades 1 and 2 peripheral neuropathies in five patients (20%), allergy in two patients, and headache in two patients. These events were self‐limited, occurring in the 48 hours after treatment and resolving within 24 hr. Three patients presented with more severe though transient side effects, one with a Grade III neuropathy and two with seizure. Eighteen patients (72%) of those treated with IT/intraventricular rituximab, with or without other CNS directed treatment, achieved a CNS remission. This case series suggests that IT/intraventricular rituximab has therapeutic efficacy and relatively limited toxicity. Prospective trials of IT/intraventricular rituximab for patients with CNS involvement of CD20 + B lymphoid malignancies are warranted. Am. J. Hematol. 91:486–491, 2016. © 2016 Wiley Periodicals, Inc.